Preparation and characterization of poly (amidoxime) chelating resin for metal ions removal from water - Siva Kumar, Supayah (2012)
The chelating ion-exchange resin containing amidoxime functional group was prepared from polyacrylonitrile (PAN) grafted kenaf fiber. The PAN grafted copolymer was obtained by free radical initiating process using ammonium ferrous sulfate as an initiator. Conversion of nitrile groups of the PAN grafted copolymers into the amidoxime was carried out by treatment with hydroxylamine under alkaline solution. Thus, the ester and nitrile groups of the PAN were converted into the amidoxime groups. The identification of amidoxime group was performed by qualitative and FT-IR analysis. An investigation was done on the chelating behavior of the prepared resin towards a series of metal ions and the binding of some transition metal ions such as copper, iron, zinc, chromium and nickel at pH 5. The rate of exchange of nickel and copper is very fast, where the adsorption capacities of metal ions by the resin were pH dependent and the rate of exchange was t 1 1 2 <9 mm.